Olahraga Hidup Baru (ORHIBA): Lowering Anxiety Level and Blood Pressure of Hypertensive Elderly - Ni Luh Putu Dian Yunita Sari; Ni Made Dwi Ayu Martini; Komang Yogi Triana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The effort to control blood pressure in the hypertensive elderly during the pandemic have not been optimal. The limitation of physical distancing also creates a new problem for the elderly, namely anxiety. The purpose of this study was to determine the effect of  ORHIBA on the level of anxiety and blood pressure in the elderly hypertensive elderly during the pandemic. This study used a quantitative approach with a quasi-experimental pre-post test design with the control group. The sampling technique used is purposive sampling by setting inclusion and exclusion criteria. The sample size obtained is 64 people (32 per group). Data were collected for four weeks and the frequency of intervention was twice a week. Blood pressure variables were not normally distributed. So that both variables were tested with the Wilcoxon test for paired data and the Mann-Whitney test for unpaired data. The results obtained are that there is an effect of ORHIBA on the level of anxiety (p-value 0.001), systolic blood pressure (p-value 0.001, and diastolic blood pressure (0.001) in the hypertensive elderly. These results can be used as a reference in providing nursing care for hypertensive elderly during the pandemic to continue to undergo physical exercise even though individually at home.Abstrak: Upaya pengontrolan tekanan darah lansia hipertensi di masa pandemi COVID-19 belum optimal. Adanya pembatasan kontak fisik juga menimbulkan masalah baru pada lansia, yaitu kecemasan. Tujuan penelitian ini adalah untuk mengetahui pengaruh latihan fisik ORHIBA terhadap tingkat kecemasan dan tekanan darah lansia hipertensi dalam masa pandemi. Penelitian ini menggunakan pendekatan kuantitatif dengan desain quasi experimental pre-post test with control group. Teknik sampling yang digunakan adalah purposive sampling dengan menetapkan kriteria inklusi dan eksklusi. Besar sampel yang didapatkan adalah 64 orang (32 orang per kelompok). Pengambilan data dilakukan selama empat minggu dan dengan frekuensi pemberian intervensi dua kali seminggu. Variabel tekanan darah tidak berdistribusi normal. Sehingga kedua variabel diuji dengan uji Wilcoxon untuk data berpasangan dan uji Mann-Whitney untuk data tidak berpasangan. Hasil yang didapatkan adalah terdapat pengaruh latihan fisik ORHIBA terhadap tingkat kecemasan (p value 0,001), tekanan darah sistolik (p value 0,001,  dan tekanan darah diastolik (0,001) lansia hipertensi. Hasil ini dapat dijadikan acuan dalam memberikan asuhan keperawatan bagi lansia hipertensi selama masa pandemi agar tetap menjalani latihan fisik walaupun secara individu di rumah.